Precise determination of the 1s Lamb Shift in hydrogen-like heavy ions at the ESR storage ring using microcalorimeters. (26th November 2015) - Kraft-Bermuth, S; Andrianov, V; Bleile, A; Echler, A; Egelhof, P; Grabitz, P; Ilieva, S; Kiselev, O; Kilbourne, C; McCammon, D; Meier, J P; Scholz, P
Abstract: The precise determination of the energy of the Lyman α 1 and α 2 lines in hydrogen-like heavy ions provides a sensitive test of quantum electrodynamics in very strong Coulomb fields. To improve the precision of such experiments, the new detector concept of microcalorimeters, which detect the temperature change of an absorber after an incoming particle or photon has deposited its energy as heat, is now exploited. The microcalorimeters for x-rays used in these experiments consist of arrays of silicon thermometers and x-ray absorbers made of high-Z material. With such detectors, a relative energy resolution of about 1 per mille is obtained in the energy regime of 50–100 keV. Two successful measurement campaigns to determine the 1s Lamb Shift in Pb 81+ and Au 78+ have been completed: a prototype array has been applied successfully for the determination of the 1s Lamb Shift of Pb 81+ at the ESR storage ring at GSI in a first test experiment. Based on the results of this test, a full array with 32 pixels has been equipped and has recently been applied to determine the 1s Lamb Shift in Au 78+ ions. The energy of the Lyman- α 1 line agrees within error bars well with theoretical predictions. The obtained accuracy is already comparable to the best accuracy obtained with conventional germanium detectors for hydrogen-like uranium.